Short Communication: Leaf architectural analysis of confusing Syzygium species: Syzygium aqueum (Burm.f.) Alston and Syzygium samarangense (Blume) Merr. & L.M.Perry (Myrtaceae) - Jose Dale III Viacrucis; Inocencio Jr. Buot (Society for Indonesian Biodiversity, 2021)
Abstract. Viacrucis III JDL, Buot Jr. IE. 2021. Short Communication: Leaf architectural analysis of confusing Syzygium species: Syzygium aqueum (Burm.f.) Alston and Syzygium samarangense (Blume) Merr. & L.M.Perry (Myrtaceae). Biodiversitas 22: 3341-3348. Among species of Myrtaceae family which has economic and ecological importance are the two Syzygium species, Syzygium aqueum and Syzygium samarangense. Both species are cultivated throughout the tropics because of their edible fruits and medicinal properties of various plant parts. However, despite their wide utilization, the two species are often confusing due to their morphological similarity. In this study, leaf architecture of S. aqueum and S. samarangense have been evaluated to delineate the two confusing taxa. Selected laminal and venation characters were compared. Results showed many similar characters shared between the two species, however, laminar size, apex and base shape, areolation, and freely ending veinlets (FEVs) were found to be distinct. Multivariate analyses, cluster analysis employing Gower similarity index, using unweighted pair-group average (UPGMA) and single linkage (nearest neighbor) algorithm, and ordination using Principal Coordinates Analysis (PCoA), illustrated that they are grouped separately. The variations in laminal and venation characters are additional set of information that will allow accurate differentiation of the two species. However, it is recommended that additional taxonomical analysis using various methods, such as molecular techniques, be employed and characters, such as floral morphology, be studied to contribute in the resolution of the taxonomic complexity of this group and other taxonomic controversies